Increasing Introverted EFL Learners’ Engagement through the Flipped Classroom Instructional Model - amani bouchareb; mustapha gasmi (biblio centrale, 2024)
The quest for effective instructional methods to enhance engagement among different personality types of English as a Foreign Language (EFL) learners is crucial in today's educational landscape. Traditional classroom settings often fail to meet the specific needs of introverted learners, who may experience higher levels of anxiety and lower participation. This study investigates the potential of the flipped classroom instructional model in enhancing academic engagement levels among introverted EFL students by aligning with their cognitive preferences and educational requirements. The case study of this research involves third-year EFL students at the English department of Guelma University. Adopting a true-experimental and mixed-methods research design, the study involved both quantitative and qualitative tools. Quantitative data were collected using the University Student Engagement Inventory (USEI) and a students’ questionnaire, while qualitative insights were gathered through the Myers–Briggs Type Indicator (MBTI), a personality test, and teachers’ interviews. Participants were divided into experimental and control groups to compare the flipped classroom model with traditional teaching methods. The experimental group consisting of 54 students was taught using the flipped classroom method while the control group involving 57 students received traditional teaching. The findings highlight several dimensions in which the flipped classroom positively impacts academic engagement; namely, behavioral, emotional, and cognitive. The structured and preparatory nature of the flipped classroom significantly reduces anxiety and boosts participation among introverted students. Additionally, the model also benefits extroverted learners, fostering an active and interactive learning environment. Consequently, the flipped classroom emerges as a promising educational strategy, improving engagement and learning outcomes for EFL students and contributing to the advancement of language education pedagogy.